Mormodes salazarii (Orchidaceae, Catasetinae), a new species with greenish-white flowers from Costa Rica - Blanco Coto, Mario Alberto (2016)
Mormodes salazarii (Orchidaceae, Catasetinae), a new species apparently endemic to Costa Rica, is described and illustrated. It is similar to M. fractiflexa because of its non-resupinate flowers, entire lip and revolute margins of sepals and petals, but differs from that species by its erect flowers (vs. pendulous) and strongly reflexed lateral sepals without colored lines (vs. widely open or slightly reflexed lateral sepals with red blurred lines).